A new species of Psephenothrips (Thysanoptera: Phlaeothripidae) from China - Tong, Xiaoli; Lau, Clive Siu-Ki; Zhao, Chao (Zootaxa, 2021)
A new species of Phlaeothripinae, Psephenothrips aporosae sp. n., is described based on specimens collected in leaf galls on Aporosa octandra [Phyllanthaceae] in China. The new species is characterized by the head being much shorter than wide, the tube slightly longer than the head, and the metanotum with close longitudinal reticulation.